A variação linguística nas aulas de língua portuguesa: um estudo à luz da sociolinguística educacional - Freitas , Anna Flávia Lenz (2022)
It is necessary to write and to discuss about issues of linguistic variation, in the classroom, due to the extreme appreciation of the grammatical tradition, which can cause linguistic prejudice that is still provoked and suffered by most part of the people. The main objective is To verify how the teachers affirm the teaching of Portuguese language occurs, in the classes of Elementary School and High School of public schools in the city of Foz do Iguaçu, regarding issues of prejudice, language variation and linguistic change. As specific objectives, we intend: I: To review the bibliographic of the theory of Sociolinguistics and its main concepts, as well as the Portuguese language teaching in Brazil, II: To carry out a survey of what Portuguese Language teachers claim to do in Portuguese Language classes regarding the issue of linguistic variation and analyze their answers according to Educational Sociolinguistic theory, revealing positive or negative value judgments in relation to the Sociolinguistic concepts and Portuguese Language Teaching and III: To think critically about the Portuguese language teaching. The development of our entire research occurred during the SARS-Cov2 pandemic and because of that, we used an online questionnaire as a data collection source. Our research is quantitativequalitative, basic, bibliographical, descriptive and has survey procedure. The objective is to describe, explain and quantify the data that has been collected. We used the theory of Sociolinguistics (Labov, 2008; 1972), as epistemological affiliation, and Antunes (2007), Bagno (1999; 2001; 2003; 2009), Bortoni-Ricardo (2004; 2005), Martelotta (2011), Tarallo (2007) and Weinreich; Labov; Herzog; (2006) who gave us the necessary theoretical support in our analyses. From our empirical experiences as a student and colleague of teachers, we have postulated that the teaching of Portuguese, present at public schools, and also in Foz do Iguaçu, was more guided by traditional grammar, ignoring the basic issues of linguistic variation and change. However, according to our analyses, only a small part of the teachers says they teach in this way. Unfortunately, it does not give us the conditions to affirm that this is the true reality, because, they are “statements” (and not “observations” made in the classroom), in many moments we observed contradictions in the answers of the teachers, resulting in the interpretation that, although it seems a large portion of the participants have sociolinguistic bases in their classes, we cannot say, in fact, if this occurs. Furthermore, due to State negligence, lack of investment and appreciation of public education, there is still a need of teachers having resources and more solid knowledge about sociolinguistic concepts and how to apply them in the classroom.